Safety and Efficacy of Tenecteplase among Patients with ST Elevated Myocardial Infarction - Experience in a Tertiary Care Hospital in Bangladesh - Rahman, Md. Mahidur; Joty, Syeda Mehbuba; Jeshan, Tanvir; Ghosh, Tamal Peter; Ahmed, Moeen Uddin; Hossain, Solaiman; Islam, KM Shaiful; Saiyara, Noshin; Islam, Faridul (Cardiology and Cardiovascular Medicine, 2023)
Introduction: The re-establishment of the blood flow to closed vessels as quickly as possible (reperfusion), is the standard treatment for ST-elevated myocardial infarction (STEMI), with the aim of preventing myocardial necrosis and preserving myocardial muscle mass in order to lower the risk of heart failure and ultimately increase the patient's survival. Aim of the study: To evaluate the safety and efficacy of Tenecteplase (TNK-tPA) among STEMI patients. Methodology & Materials: This was an observational study and was conducted in the Department of Cardiology, Enam Medical College Hospital, Dhaka, Bangladesh during the period from 1 July 2022 to 30 June 2023. In our study, we took 50 patients diagnosed with either ST elevated Myocardial Infarction or new onset LBBB in ECG. Result: Among the study population, duration of chest pain was 5.21 ± 3.05 hours. We found the overall rate of clinically successful thrombolysis (CST) with TNK was 90.0%. Patients who got TNK within 03 hours had CST rate of 96.30% compared to patients who got delayed TNK treatment (86.67% CST, >6 hours from onset of pain). Chest pain resolution was found in 92% patients following pharmacological fibrinolysis with TNK. About 90% of patients had at least 50% resolution of ST elevated segments at 90 minutes. About 10% had hemoptysis, 6% had gum bleeding & arrhythmia, and only 1(2%) had fatal intra-cerebral haemorrhage (ICH) who eventually died. Conclusion: Our findings indicate that reperfusion therapy with TNK-tPA is the best fibrinolytic treatment option for STEMI patients with relatively few side-effects profile.